A Study on Family Buying Behaviour with Refernce to Health Drinks in Ghaziabad Market - Rai, Neel; Sijariya, Rajeev (Journal of Commerce and Trade, 2018)
The Purpose of this study is to investigate the family role and their buying role with reference to health drinks and also to find out whether TV advertisements are more effective than other modes of advertisement or not. It is to analyze that family take decision in buying health drinks or children take. T.V. advertisement as compared to other means are more effective than other modes of advertisements. Research Methodology: In this research the researcher applied the descriptive research & the sources of data was primary & secondary. The primary data was collected in the form of questionnaire and thus happen to be an original in character. Where as the secondary data was collected from internet and also through other various business magazines too. The researcher investigated in the form of his findings and conclusions that decisions in family are not taken by the family members, as some decision are also taken by the children of that family. So companies have targeted to focus both the categories in their ads to show their health drink ads on children TV channels or cartoon channels also other family channels too. Researcher also find that the low cost or price of health drinks cannot affect the buying behaviour of parents or family. As According to the result of the test TV advertisement are more effective than other modes of ads so companies have to pay more attention on TV advertisement trends. Classification-JEL : R11, R31, R41